Otomasi Perencanaan Produksi Pada Sekolah - Sanjaya, Dwi Haris; Firmansyah, Yoga; Anam, Moch. Irsyadul; Yaqin, M. Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Production planning is very important in business processes. Production planning aims to minimize the total cost of production. In this research, automation of production planning is done using data obtained based on school business processes. The purpose of this study is to determine the best production costs for the smooth production process of schools. This research uses descriptive research. Descriptive research aims to obtain information in the implementation of school business process planning. The calculation of production costs in this study uses the Activity Based Costing (ABC) technique and is carried out using Microsoft Excel. The calculation of this research is done by first determining the total target and raw materials from the school production process, then calculating the production costs of this school production process. The results of these calculations found that the optimal production cost for each student of a total of 300 students during the 3-year learning period is Rp. 605,728. From this study, it is also known that the total number of students and labor directly affects the amount of production costs.